KESANTUNAN BERBAHASA KEPALA SEKOLAH DASAR INPRES KOTARINDAU DALAM SITUASI FORMAL - Hikmawati, Andi (BAHASANTODEA, 2016)
The objective of this research is to describe Language behavioring of the head master at SD Inpres Kotarindau in formal situation, it is include (1) behavioring form of the head master at SD Inpres Kotarindau in formal situation, (2) behavioring strategy of the head master at SD Inpres Kotarindau in formal situation. The approach which used in this research is prakmatik approach. The method which used is qualitative descriptive method. The data accumulation is done by two techniques, they are (1) recording and (2) observation. The data analysis technique in this research is interactive model. The analysis in this research include four steps, they are (1) data accumulation, (2) data of reduction, (3) serving of data, (4) verification or take a concluding. The result of this research consist of (1) behavioring form in invitation, (2) behavioring form in requesting, (3) behavioring form in wish, (4) behavioring form in attitude, (5) behavioring form in advice, and (6) behavioring form in hope. Second, the behavioring function of head master in formal situation include (1) behavioring function of invitation is functioned by invitation and attention, (2) behavioring function of requesting is fuctioned by action and confirmation, (3) behavioring function of hope is functioned by hope, and (4) behavioring function in advice is functioned as a prohibit. Third, the strategy of language behavioring of head master in formal situation include diect strategy and indirect strtegy. Direct strategy consist of (1) direct invitation, (2) direct advice, (3) direct hope, and (4)Â direct request. The strategy of indirect consist of indirect command.